Stagnation of glymphatic interstitial fluid flow and delay in waste clearance in the SOD1-G93A mouse model of ALS. (October 2021) - Hirose, Mikako; Asano, Mito; Watanabe-Matsumoto, Saori; Yamanaka, Koji; Abe, Yoichiro; Yasui, Masato; Tokuda, Eiichi; Furukawa, Yoshiaki; Misawa, Hidemi
Highlights: AQP4 deficiency in ALS model mice promotes accumulation of toxic SOD1 species. SOD1 oligomers are excreted via the glymphatic system. The glymphatic system is aberrant in SOD1 G93A mice. Improvement of the glymphatic system may be a new therapeutic target for ALS. Abstract: Overexpression and mislocalization of aquaporin-4 (AQP4) in the SOD1 G93A mouse model of amyotrophic lateral sclerosis (ALS) have previously been reported. However, how alterations of AQP4 affect interstitial bulk flow in the brain and spinal cord, the so-called glymphatic system, is unclear. Here, we report an enhanced accumulation of disease-associated SOD1 species including SOD1 oligomers in SOD1 G93A ;AQP4 −/− mice compared with SOD1 G93A mice during ALS disease progression, as analyzed by sandwich ELISA. By directly injecting SOD1 oligomers into the spinal cord parenchyma, we observed a significantly larger delay in clearance of biotinylated or fluorescent-labeled SOD1 oligomers in AQP4 −/− mice than in wild-type mice. Furthermore, when we injected the fluorescent-labeled tracer protein ovalbumin into the cisterna magna and analyzed the tracer distribution in the cervical spinal cord, approximately 35 % processing ability was found to be reduced in SOD1 G93A mice compared to wild-type mice. These results suggest that the glymphatic system is abnormal and that waste clearance is delayed in SOD1 G93A mice.